Comparative Study Of Ship Loading And Unloading Methods To Increase Productivity In Large Ports (Maritime Park: Journal of Maritime Technology and Society, 2025)
This research examines the comparison between manual ship loading and unloading methods and modern technology in the context of large ports to increase productivity. The main focus of the study is to evaluate the effectiveness of each process in improving port operational efficiency. The research was carried out through analysis of quantitative and qualitative data collected from large ports that apply both methods. Data collected includes loading and unloading times, operational costs, and productivity. The research results show that ports that use modern technology such as gantry cranes and automated guided vehicles (AGV) experience a significant increase in productivity compared to ports that use manual methods. Modern methods can reduce loading and unloading times by up to 30% and reduce operational costs substantially. In addition, this technology also reduces the risk of errors and damage to goods, increases safety, and optimizes resource use. These findings indicate that investment in modern technology is a strategic step to increase efficiency and productivity in large ports. Therefore, port managers should consider the implementation of advanced technologies and staff training to maximize the benefits of these technologies. It is hoped that this research can provide practical guidance for ports in designing more efficient and economical loading and unloading strategies.
Keywords: Ship Loading and Unloading; Efficiency; Productivity; Modern Technology; Manual Method